Pengaruh Pad, Belanja Modal Dan Angkatan Kerja Terhadap Pdrb Per Kabupaten/Kota Di Provinsi Bali - Lestari, Sri Eka; Budhi, Kembar Sri (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 3, No. 12, Desember 2014 (pp. 549-623), 2014)
Economic growth is one indicator that is commonly used in determining the success of development. Economic growth is measured by the value of GDP of a region or area. Gross Domestic Product (GDP) is one of the indicators that describe the rate of economic growth is the rate of economic growth is usually also used to assess how far the successful development of an area within a specified time period and become a benchmark in determining the direction of future development policies. The purpose of this study was to determine the direct effect of the labor force to GDP and also to determine the effect of indirect revenue and capital expenditure to GDP through the development expenditure. The data used in this study were obtained at the secondary Central Bureau of Statistics. The data analysis technique used in this study is the analysis of the path (path analysis). The results of data processing show expenditure and workforce development has a direct impact on GDP meanwhile, revenue and capital expenditure has indirect influence through development expenditure to GDP. The results of the regression coefficient R 2 in this study was 0.87, which means 87% of the information contained can be explained by a model that formed while the remaining 13% is explained by other variables outside the model established.
Keywords: regional grow domestic product, local revenue, capital expenditure, workforce development spending